Early weaning completely eliminates porcine cytomegalovirus from a newly established pig donor facility for xenotransplantation. (18th August 2018) - Egerer, Stefanie; Fiebig, Uwe; Kessler, Barbara; Zakhartchenko, Valeri; Kurome, Mayuko; Reichart, Bruno; Kupatt, Christian; Klymiuk, Nikolai; Wolf, Eckhard; Denner, Joachim; Bähr, Andrea
Abstract: For clinical xenotransplantation, transplants must be free of porcine cytomegalovirus (PCMV). Piglets become infected primarily in the perinatal period by the mother sow. While individual donor animals can be protected from infection by isolation husbandry, success is not guaranteed and this strategy poses the risk of undetected infections and raises animal welfare questions. Here, we present the establishment of a completely PCMV‐negative pig herd for breeding donor animals for xenotransplantation. Eleven pregnant DanAvl Basic hybrid sows were purchased from a designated pathogen‐free (DPF), PCMV‐positive colony and transferred to a new pig facility at the Centre for Innovative Medical Models (CiMM) 4 weeks prior to farrowing. At the age of 24 hours, piglets were early‐weaned and transferred to a commercially available Rescue Deck system dedicated to motherless rearing of piglets. Sows were removed from the facility. The PCMV status of F1‐generation animals was determined at regular intervals over a period of 14 months by a sensitive real‐time PCR‐based detection method testing blood, nasal swabs and cultured peripheral blood mononuclear cells (PBMCs). F1 sows were used as recipients of genetically modified embryos to generate a xenotransplant donor herd. Offspring were tested for PCMV accordingly. All offspring have remained PCMV negative over the whole observation period of 14 months. A completely PCMV‐negative pig herd for xenotransplantation has thus been successfully established.